2016
DOI: 10.1002/2211-5463.12069
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamics of monomeric, dimeric, and tetrameric α‐synuclein structures in water

Abstract: Human α‐synuclein (αS) is an intrinsically disordered protein associated with Parkinson's disease. Molecular mechanisms of corruptive misfolding and aggregation of αS resulting in the disease, as well as the structure and other properties of the corresponding oligomers are not entirely understood yet, preventing the development of efficient therapies. In this study, we investigate the folding dynamics of initially unfolded hypothetical αS constructs in water using all‐atom molecular dynamics simulations. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 73 publications
(176 reference statements)
0
25
0
Order By: Relevance
“…Further studies are required to further clarify which cluster might promote dimer formation. Previous simulations suggested that the β-strand-rich hydrophobic NAC segment is important for dimerization 1 . Since the centroid structure of cluster 1 has an exposed hydrophobic β-sheet that is extended, cluster 1 might be the potential structural subpopulation that promotes dimerization (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further studies are required to further clarify which cluster might promote dimer formation. Previous simulations suggested that the β-strand-rich hydrophobic NAC segment is important for dimerization 1 . Since the centroid structure of cluster 1 has an exposed hydrophobic β-sheet that is extended, cluster 1 might be the potential structural subpopulation that promotes dimerization (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…α-Synuclein (α-syn) is a 140-residue protein containing an N-terminal segment (residues 1~60), a hydrophobic non-amyloid-β component (NAC) segment (residues 61~95), and an acidic C-terminal segment (residues 96~140) 1 . It is encoded by the SNCA gene in humans and is mainly expressed in the presynaptic terminals of neurons 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the effect of TMAO on unfolded α-synuclein was studied and observed that TMAO caused folding of the peptide in biphasic manner (Uversky et al, 2001 ). Mane and Stepanova ( 2016 ) investigated the folding dynamics of alpha-synuclein in initially unfolded form in water using an all-atom molecular dynamics simulations and essential dynamics (Mane and Stepanova, 2016 ). The synuclein constructs included a monomer, dimer and a tetramer.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium and chloride ions were added to neutralize the positive charge of the peptide. The choice of using sodium chloride is based on the large number of previous molecular dynamics studies on alpha-synuclein where sodium chloride has been used (Herrera et al, 2008 ; Cino et al, 2012 ; Tian et al, 2012 ; Vekrellis and Stefanis, 2012 ; Vermaas and Tajkhorshid, 2014 ; Mane and Stepanova, 2016 ). Long range electrostatic interactions were computed using Particle Mesh Ewald method (Darden et al, 1993 ; Essmann et al, 1995 ) with a grid spacing of 0.12.…”
Section: Methodsmentioning
confidence: 99%
“…They found that TMAO induced the α-synuclein to fold back to compact conformation and suggested a biphasic mechanism of α-synuclein [135]. Another group used an all-atom molecular dynamic simulations and essential dynamics approach to study the dynamics of folding of unfolded α-synuclein present in water [136]. They used a monomer, dimer, and a tetramer of α-synuclein forms in their study.…”
Section: Effects Of Osmolytes On α-Synucleinmentioning
confidence: 99%